Allergic contact stomatitis (stomatitis venenata): A case report of oral hypersensitivity reaction to toothpaste (Indian Journal of Case Reports, 2019)
Allergic contact stomatitis (stomatitis venenata) might resemble oral lichen planus or oral lichenoid lesion clinically which can be acute or chronic in nature. Many offending agents have been attributed to their development and the most common being dental restorative materials, lipstick or flavouring agents in toothpaste or chewing gums. Allergic reactions can be in mild form to life-threatening anaphylaxis. The identification of the exact cause for allergy is difficult. Here, we report the case of a 37-year-old patient who presented with allergic contact stomatitis to a conventional daily routine product. Importance of history taking and awareness by the clinician about the contents of any new products being prescribed to the patient are emphasized by this case report.